Experience as a target of client-centered psychotherapy - Kocharian, Oleksandr (Psychological Counseling and Psychotherapy)
The article deals with the variety of client-centered practice, and emphasizes that it were serious transformation in Carl Rogers’s work from the client support strategy in the depth of his problems to support strategy in depth experience. The bases of the client’s problems are "mash" experiences that have specific characteristics that distinguish them from normal emotions. The task of psychotherapy is to help clients release the "mash" of emotions and increase the intensity of the emotional process. The emotional topography model of the psyche is considered as a mechanism of psychotherapy for balancing the emotions. Keywords: person-centered psychotherapy, mechanisms of psychotherapy, experience, the characteristics of the fixed experience, the topography of the psyche.